Design, Development, and Characterization of Film Forming Spray as Novel Antifungal Topical Formulation for Superficial Fungal Infections - Desai, Mrunal; Godbole, Ajeet M; Somnache, Sandesh; Gajare, Pankaj; Pednekar, Arti; Manerikar, Siddhi; Kudaskar, Krutika; Naik, Vivek (Indian Journal of Pharmaceutical Education and Research, 2022)
Introduction: Miconazole Nitrate is prescribed as an antifungal agent in conventional dosage forms. To mask the disadvantages of sticky creams and their tendency to rub off, an intelligent dosage regimen needs to be designed. Objectives: The present study aimed to design, develop, and characterize Miconazole Nitrate (0.5% w/v) film-forming spray for the treatment of superficial fungal infections in nails, such as Tenia and Onychomycosis. Materials and Methods: Eutectic mixture of Menthol and Camphor in the ratio of 1:1 was used to enhance permeation and solubilize film-forming polymers, i.e., Eudragit L-100 and Ethyl Cellulose, and provide a cooling effect. Results: The prepared formulations were evaluated for various critical parameters, and based on the results obtained, Formulation F1 exhibited a drug content of 91.82% and 83.75% of % Cumulative drug release through Eggshell membrane and was found to be the best-suited formulation. Formulation F1 was further chosen for carrying out in-vitro permeation studies through shed snakeskin of Ophiophagus Hannah (Cobra), which gave % a cumulative drug release of 72.453 %, exhibited pH of 5.8 and evaporation time of four minutes yielding a non-sticky film. The prepared formulations were clear in appearance and formed Uniform, non-sticky, flexible films. The average time required for the release of 50% drug was found to be 120-180 min, and the drug transport kinetic was best fitted into the Korsmeyer’s-Peppas model. Conclusion: The study concluded that the prepared transdermal film-forming spray formulations would be efficient for treating fungal infections of superficial nature and will prove to be a practical approach in the delivery of topical antifungal agents.
Keywords: Fungal Infections; Film-forming Spray; Miconazole Nitrate; Antifungal; Eutectic Mixture